GA Houses 5. - Futagawa, Yukio; Gualdoni, Flaminio; Sharp, Dennis; Uyeda, Makoto (Tokyo : A.D.A. EDITA, Tokyo Co., Ltd., 1978)
Renovations and Apartment's Interiors : Works by Soane, Salvati & Tresoldi, Meier, Graves and others
Engelse en Japanse tekst
boek
Keywords: AFRa; Bicocchi, Giancarlo; Bicocchi, Luigi; Chimacoff, Alan; Graves, Michael; Gregotti; Grover, William H; Harnden, Peter Graham; Hardy, Hugh; Harper, Robert L; Holzman, Malcolm; Lyndon, Donlyn; Mangiarotti, Angelo; Meier, Richard; Monsani, Roberto; Moore, Charles Willard; Morassutti, Bruno; Pampo, Chiara; Peterson, Steven; Pfeiffer, Norman; Rudolph, Paul; Salvati, Alberto; Scarpa, Afra; Scarpa, Tobia; Smith, C. Ray; Soane, John; Stern, Robert A.M.; Tiravanti, Lanfranco Bombelli; Tresoldi, Ambrogio; Turnbull, William Jr; Vedensky, Dmitri; Vigo, Nanda; Whitaker, Richard R. Jr